Effect of detergents from laundry greywater on soil properties: a preliminary study - Mohamed, R. M.; Al‑Gheethi, A. A.; J., Noramira; Chan, C. M.; M. K., Amir Hashim; M., Sabariah (Springer Nature, 2018)
Detergent compounds are classes of the organic micro-pollutants in the laundry wastewater. The disposal of these compounds into the soil has several adverse efects on their composition. In the present study, changes in the soil characteristics, which included saturated hydraulic conductivity (Ksat), EC, pH, exchangeable sodium percentage, cation exchange capacity (CEC), and sodium adsorption on ratio were examined after the irrigation with laundry wastewater. Ten clothes were washed with one full cap of powder (PLD) and liquid laundry (LLD). Laundry greywater samples were used for the irrigation of soil. The results revealed that the pH of soil increased from 3.85 to 4.42 and 4.09 after irrigation by PLD and LLD greywater, respectively. The EC of the irrigated soil increased from 50.32 to 152.5 and 147.6 μS/cm, respectively. The CEC was raised to 79.93 and 41.39 meq/100 g, while Ksat was reduced to 7.38 × 10−10 and 7.11 × 10−10 cm/s, respectively. These fndings highlighted the negative efects of laundry greywater discharge on soil properties.